Liberation of SARS-CoV main protease from the viral polyprotein: N-terminal autocleavage does not depend on the mature dimerization mode - Chen, Shuai (Protein Cell, 2010)
The main protease (M(pro)) plays a vital role in proteolytic processing of the polyproteins in the replicative cycle of SARS coronavirus (SARS-CoV). Dimerization of this enzyme has been shown to be indispensable for transcleavage activity. However, the auto-processing mechanism of M(pro), i.e. its own release from the polyproteins through autocleavage, remains unclear. This study elucidates the relationship between the N-terminal autocleavage activity and the dimerization of “immature” M(pro). Three residues (Arg4, Glu290, and Arg298), which contribute to the active dimer conformation of mature M(pro), are selected for mutational analyses. Surprisingly, all three mutants still perform N-terminal autocleavage, while the dimerization of mature protease and transcleavage activity following auto-processing are completely inhibited by the E290R and R298E mutations and partially so by the R4E mutation. Furthermore, the mature E290R mutant can resume N-terminal autocleavage activity when mixed with the “immature” C145A/E290R double mutant whereas its trans-cleavage activity remains absent. Therefore, the N-terminal auto-processing of M(pro) appears to require only two “immature” monomers approaching one another to form an “intermediate” dimer structure and does not strictly depend on the active dimer conformation existing in mature protease. In conclusion, an auto-release model of M(pro) from the polyproteins is proposed, which will help understand the auto-processing mechanism and the difference between the autocleavage and trans-cleavage proteolytic activities of SARS-CoV M(pro).